Mixed hepatoblastoma and teratoma of the liver in a 3-year-old child: a unique combination and clinical challenge - Leuschner Ivo; Hirsch Wolfgang; Till Holger; Bierbach Uta; Krenauer Alexander; Moll Alexander; Schmitz Nicole; Wittekind Christian; Aigner Thomas (BMC, 2009)
Abstract Primary liver tumors in children are rare with malignant hepatoblastoma being the most common neoplasm. In this report, we describe the diagnosis and clinical management of a large liver tumor in a 3-year-old child that displayed the features of both, conventional hepatoblastoma and malignant teratoma. Pathological assessment on a pre-operative bioptical specimen showed an immature teratoid tumor with no area of hepatoblastic differentiation present. Histological and immunhistological examination of the resected tumor specimen additionally showed tumor areas of very different differentiation pattern intermixed with each other, namely areas of hepatoblastoma-typical and neuroblastoma-like morphology as well as areas of rhadomyosarcomatous differentiation. After chemotherapy the tumor size increased and an extended right hemihepatectomy was performed. Post-operatively, the general condition of the child improved and adjuvant chemotherapy was started two weeks later. 36 months after initial diagnosis the patient is healthy, in good general condition, and without any sign of residual tumor disease. Overall, we describe the diagnosis and clinical management of a large liver tumor in a 3-year-old child that displayed the features of both, conventional hepatoblastoma and malignant teratoma and was designated as mixed hepatoblastoma and teratoma. Though mesenchymal tumor portions can occur within hepatoblastomas, most commonly osteoid or chondroid, our case is different as it presents a large spectrum of mesenchymal and epithelial differentiation pattern in most of the lesion.